Reducing the costs of paediatric antibiotic prescribing in the community by implementing guideline recommendations. (24th April 2013) - Piovani, D.; Clavenna, A.; Sequi, M.; Cartabia, M.; Bortolotti, A.; Fortino, I.; Merlino, L.; Bonati, M.; ,
Summary: What is known and objective: Italian children receive a high number of antibiotic prescriptions, and the use of second‐choice antibiotics is common. A few studies in other countries have demonstrated that the implementation of international guidelines for the most common paediatric diseases may reduce the associated costs. A cost analysis of the expenditure for antibiotic prescriptions in outpatient children in the Lombardy region (Italy) and for each of the region's local health units (LHUs) was performed using a pharmacoepidemiological approach. The safety and cost impact associated with a quali‐quantitative improvement in antibiotic prescribing was estimated. Methods: The data source was the Lombardy region's prescription database (year 2008) for outpatient children <14 years old. The average total expenditure for each package, and per capita, was calculated for each active substance considered and for each LHU. An estimate of the possible cost reduction was elaborated using, as a reference, the prescription profile of a group of paediatricians that has been involved in initiatives concerning care for years. The hospital admission rates for acute respiratory infections (ARI) and their major complications were evaluated at the regional level and in the group of children followed by the reference paediatricians. Results and discussion: The cost reduction estimate reveals a possible decrease in antibiotic expenditure of about 3·6 million euros (−19·5%) in the Lombardy region. Large variability was observed between different LHUs (−33·3 to +9·2% of difference). The hospital admission rate was not different when comparing the group of children followed by the reference paediatricians to the rest of the study population, but the hospital admission rate for ARI was lower in the reference group (χ 2 = 16·4, P < 0·001). What is new and conclusion: This is the first Italian study to evaluate the costs related to a specific prescription profile, which already exists in the real setting, hypothesizing its application in a large outpatient child population of the same geographical area. The results show that by improving prescribing appropriateness, it is possible to reduce the expenditure associated with antibiotic prescriptions to outpatient children in the Lombardy region by about one‐fifth. The lower rate of hospital admissions for ARI suggests that the adopted profile is also beneficial to children's health.